Equity-centered knowledge brokering: taking stock of challenges, strategies, and possibilities - Malin, Joel R.; Shewchuk, Samantha (Frontiers in Education, 2024)
The pursuit of equity is a cornerstone of progress across diverse fields. Emerging literature across several fields has begun to focus on how knowledge brokers can take an equity-centered approach. This narrative synthesis draws upon that literature to explore what it means to be an equity-centered knowledge broker and to consider the challenges and possibilities inherent in that role. It identifies critical equity issues/dimensions vis-à-vis five main brokering strategies. From this review, the strategy facilitating relationships emerges as a first-order strategy for equity-centered brokers, with impacts stretching into all other areas. Therefore, equity-centered brokers should attend heavily to developing authentic, trusting relationships, value diversity, and elevate multiple forms of knowledge. This article also highlights some challenges and ongoing tensions relevant to equity-centered brokering. Relational, equity-centered knowledge brokering is time- and resource-intensive. Likewise, ongoing debates center on the merit of assuming a neutral brokering posture. Overall, it is hoped this article will benefit knowledge brokers, those with whom they partner, and those scholars who seek to understand and support them.